The Ocean's Impact on Slow Slip Events. Issue 14 (13th July 2020) - Gomberg, J.; Baxter, P.; Smith, E.; Ariyoshi, K.; Chiswell, S. M.
Abstract: We test the hypothesis that ocean seafloor pressures impart stresses that alter the initiation or termination of transient slow slip events (SSEs) on shallow submarine and near‐coastal faults, using simulated seafloor pressures and a new catalog of SSEs in the Hikurangi subduction zone. We show that seafloor pressures may be represented by an average time history over the 100‐km dimensions of the study area. We account for SSE uncertainties and the multiplicity of processes that affect SSEs statistically by estimating the probabilities of rejecting the null hypothesis that SSE initiation or termination pressures are those to be expected by chance sampling of known (modeled) seafloor pressures, with low probabilities indicating some causal connection. No impact of ocean pressure changes on SSE initiation is detectable, but a correlation with their terminations is suggested. SSE slip that weakens the fault and makes it more sensitive to small stress changes may explain results. Plain Language Summary: The ocean waters may impart stresses that change how shallow submarine and near‐coastal faults start or stop slipping, particularly when they slip slowly over days to months (in episodes called slow slip events or SSEs). We can now assess this possibility using new simulated seafloor pressures and a catalog of SSEs in the Hikurangi subduction zone, encompassing the onshore and offshore region of northeastern New Zealand. We only ask how probable this causal connection is because SSEs are difficult to measure precisely and many physical processes may change their behaviors. Our statistical analyses do not reveal any impact of ocean pressure changes on how or when SSEs start, but do indicate they may affect when SSEs end. One explanation of this result is that the slow slippage actually causes the fault to become weaker, making it more sensitive to the small stress changes imparted by the ocean. Key Points: Ocean water column changes may affect how and when Hikurangi shallow slow slip events end, but have no detectable impact on their starts Transient slow slip events may weaken faults, making them more sensitive to small stress changes (Sparse noisy geodetic data and the emergent nature of slow slip events challenge generation of an accurate comprehensive regional catalog